Pembinaan Karakter Jujur, Disiplin, dan Bersahabat Siswa melalui Permainan Kepramukaan Di SDN Batuceper 1 - Robiansyah, Firman; Alfarisa, Fitri; Fitriani, Anes (Jurnal Gentala Pendidikan Dasar, 2024)
Education plays an important role in shaping students’ character into better individuals. Character building, especially for elementary school students, is a strategic effort, as elementary education serves as the most fundamental foundation for students’ success at higher levels of learning. This study aims to identify, analyze, and describe the implementation process of scouting game activities and their implications for fostering honesty, discipline, and friendliness among students at SDN Batuceper 1. This study employed a qualitative approach using a case study method. The subjects of this study included third- and fourth-grade students, scout trainers, scout leaders, and the principal of SDN Batuceper 1. Data were collected through observation, interviews, and questionnaires. The data analysis techniques consisted of data reduction, data display, and conclusion drawing/verification. Data validity was ensured through technique triangulation. The results of the study show that the implementation of scouting games includes several stages: pre-activity conditioning, explanation of game rules, the game process, and clarification of the game objectives. The games conducted included collaborative drawing, rafting simulation, and line formation activities. Based on the questionnaire results, 85% of the responses were categorized as appropriate, while 15% were categorized as inappropriate. It can be concluded that scouting games have a significant implication for fostering students’ character, particularly in terms of honesty, discipline, and friendliness.